2019
DOI: 10.3390/s19235265
|View full text |Cite
|
Sign up to set email alerts
|

Data Uploading Strategy for Underwater Wireless Sensor Networks

Abstract: Underwater wireless sensor networks (UWSNs) have become a popular research topic due to the challenges of underwater communication. The existing mechanisms for collecting data from UWSNs focus on reducing the data redundancy and communication energy consumption, while ignoring the problem of energy-saving transmission after compression. In order to improve the efficiency of data collection, we propose a data uploading decision-making strategy based on the high similarity of the collected data and the energy co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…It follows an object‐oriented design style and supports 3D deployment. Our proposed scheme ADMSDG is compared with existing efficient data gathering schemes EDG 18 and DUDMM 19 . The performance is evaluated based on the metrics data collection delay, accuracy and residual energy.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It follows an object‐oriented design style and supports 3D deployment. Our proposed scheme ADMSDG is compared with existing efficient data gathering schemes EDG 18 and DUDMM 19 . The performance is evaluated based on the metrics data collection delay, accuracy and residual energy.…”
Section: Resultsmentioning
confidence: 99%
“…Here, it assumes that all the sensor nodes are static. Huang et al 19 have suggested a data transmitting approach based on the high resemblance and data compression of the gathered data. This approach based on decision making proficiently enhances the energy depletion of the systems.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Wan et al [20] suggested an energy efficient scheme based on multilevel cluster selection criteria which aim to choose cluster head according to high residual energy and less radius from sink. An energy efficient routing protocol based on clustering is simulated in [21] for UWSNs. Authors proposed that clustering technique is useful to reduce energy resources consumption for a sensor network.…”
Section: Relevant Research Workmentioning
confidence: 99%
“…In [14], network lifetime of UWSNs is maximized by the assistance of sink mobility with geographic routing protocol. A reliable energy efficient routing protocol based on clustering is simulated [15] for UWSNs. Authors proposed that clustering technique is useful to reduce energy resources consumption for a sensor network.…”
Section: Relevant Research Workmentioning
confidence: 99%